Hubungan antara Pengetahuan, Status Gizi dan Pola Menstruasi pada Mahasiswi Kebidanan yang Mengalami Anemia - Azrida M; Suchi Avnalurini Sharief (FORIKES, 2021)
Anemia is a common nutritional problem in the world, especially in developing countries. One of the indicators to determine the nutritional status of adolescents is by calculating the Upper Arm Circumference (UAC) and Body Mass Index (BMI). Menstruation experienced by young women normally lasts 2-7 days each month which can increase the incidence of anemia. The purpose of this study was to determine whether there was a relationship between knowledge, nutritional status and menstrual patterns on the incidence of anemia in midwifery students. This type of research was analytic observational study with cross-sectional approach. The population in this study were 81 female students. The sample in this study were 47 students, selected using total sampling technique. The results of this study indicate that there was no relationship between knowledge and the incidence of anemia, there was no relationship between nutritional status and the incidence of anemia and there was relationship between menstrual patterns and anemia.Keywords: adolesence; anemia; knowledge; nutritional status; menstrual patternsABSTRAKAnemia merupakan salah satu masalah gizi yang umum terjadi di dunia, terutama di negara berkembang. Salah satu indikator untuk menentukan status gizi remaja adalah dengan menghitung Lingkar Lengan Atas (LILA) dan Indeks Massa Tubuh (IMT). Menstruasi yang dialami remaja putri secara normal berlangsung 2-7 hari setiap bulannya yang dapat meningkatkan kejadian anemia. Tujuan penelitian ini untuk mengetahui hubungan antara pengetahuan, status gizi dan pola menstruasi terhadap kejadian anemia pada mahasiswi kebidanan. Jenis penelitian yang digunakan adalah studi observasional analitik dengan pendekatan cross-sectional. Populasi pada penelitian ini sebanyak 81 mahasiswi. Sampel pada penelitian ini sebanyak 47 mahasiswi yang dipilih dengan teknik total sampling. Hasil penelitian menunjukkan bahwa tidak ada hubungan antara pengetahuan dengan kejadian anemia, tidak ada hubungan antara status gizi dengan kejadian anemia dan ada hubungan antara pola menstruasi dengan kejadian anemia.Kata kunci: remaja; anemia; pengetahuan; status gizi; pola menstruasi